I walk through my life with a Romani heart - de Juan, Elizabeth Infante (Romano džaniben, 2021)
The author, an Argentinian Romani activist and a member of a local evangelical movement describes the projects that she has initiated or has taken part in (exhibition, conference, demographic survey, ceramic workshop, humanitarian aid during the Covid-19 pandemic). Through these activities, she attempts to make the Romani community in Argentina more visible to the general public.
Keywords: Roma; Argentina; activism; covid-19